Das „gläserne Schlachtfeld“ als soziotechnologisches Leitbild der modernen US-amerikanischen Kriegführung - Benedix, Jan (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2006)
The Information Revolution has leveraged the attention which the academic discourse is paying to the impacts of information and communication technologies, although aspects of how to conceptualize these impacts theoretically are insufficient. Focusing on the role of IT during the rearmament of the US-military since the end of the Cold War a neogramscian perspective on the genesis and diffusion of IT as “political project” is outlined. IT gives a new model of warfare and contributes to the significant consent which the rearmament of the US-military has gained among US-citizens.